Business Constraints and Growth Potential of Micro and Small Manufacturing Enterprises in Uganda - Esther K. Ishengoma; Robert Kappel (German Institute of Global and Area Studies (GIGA), 2008)
Ugandan micro- and small enterprises (MSEs) still perform poorly. The paper utilizes data collected in Uganda in March and April 2003 to analyze the business constraints faced by these MSEs. Using a stratified random sampling, a sample of 265 MSEs were interviewed. The study focuses on the 105 manufacturing firms that responded to all questions. It examines the extent to which the growth of MSEs is associated with business constraints, while also controlling for owners' attributes and firms' characteristics. The results reveal that MSEs' growth potential is negatively affected by limited access to productive resources (finance and business services), by high taxes, and by lack of market access. – – Ugandische Kleinst- und Kleinunternehmen (KKU) des verarbeitenden Sektors entwickeln sich nur sehr schwach. Ihr Beitrag zum industriellen Wachstum ist gering. Basierend auf einer Datenerhebung von 265 KKU im März und April 2003 untersucht diese Studie die Wachstumshindernisse von KKU in Uganda. Sie analysiert, in welchem Umfang das Wachstum durch spezifische Faktoren beeinträchtigt wird. Die Ergebnisse werden in verschiedenen Regressionen u. a. mit Firmeneigenschaften kontrolliert und zeigen, dass sich hohe Steuern, ein eingeschränkter Marktzugang sowie der erschwerte Zugang zu produktiven Ressourcen in den Bereichen Finanzen und Dienstleistungen negativ auf das Wachstum von KKU auswirken.
Keywords: D21; E26; G38; H25; L25; L26; L6; O12; O14; 330; small enterprises; informal sector; growth; manufacturing; Uganda; productivity; business services